Bordering and scaling Northeast Asia. Issue 2 (3rd July 2021) - Boyle, Edward; Iwashita, Akihiro
ABSTRACT: This article utilizes an interdisciplinary border studies perspective in order to explain the absence of regional integration in Northeast Asia. While in other parts of the world, such as Europe or Southeast Asia, the cessation of the Cold War and increasing cross-border linkages promoted the emergence of integrative institutions and imagined regional communities, this has not occurred in Northeast Asia. Although the region experienced a veritable explosion of cross-border activity in the aftermath of the Cold War, potentially beneficial effects of economic and migratory flows for inter-state relations have not led to comparable success constructing regional institutions. The central issue with which the article is concerned is to understand the role of borders in this marked absence of regional integration. The paper adopts a pluralistic perspective on Northeast Asia's borders that considers them as institutions existing between states, processes of exchange and mobility over them, and as constituting the region as a borderland space characterized by functionally and spatially extensive contestation over state and regional boundaries. Border studies allow us to analyze the Northeast Asian region from the edges of both its constituent states and the region itself, and thus offers a multi-layered lens through which to examine this space. The historical and comparative analysis conducted here reveals the dynamics of regional development and constraints under which the region operates. The paper suggests that the contrast between the Northeast Asia's sharp, securitized, internal borders, multiplying into novel spaces, and its undetermined outer ones accounts for the failure to integrate today.